REGULASI EMOSI SISWA DALAM PEMBELAJARAN DARING - Chofalina Ayuningtiyas (Dharmas Education Journal (DE_Journal), 2020)
This research is based on by the existence of the Covid-19 pandemic, which raises various problems, especially the implementation of distance learning so that students are required to carry out learning online. The problem reveals that how to regulate emotions in class XI SMA Negeri 1 Comal in online learning. The purpose to be achieved of this study is at determining whether students' emotional management is able to emerge positive emotions or even generate negative emotions. This type of research was a qualitative research with a case study method. Respondents in this study were 3 students of class XI SMA Negeri 1 Comal, 3 parents as respondents, 3 close friends as respondents, 1 teacher as guidance and counseling, and 3 teachers / homeroom teachers as the respondents. The data of this study were obtained through interviews, observation, and supported by documentation. Based on the results of research data analysis, that subjects 1 and 2 are able to regulate emotions, this can be seen from the characteristics of subjects 1 and 2 being able to control themselves, being able to adapt to online learning situations. Whereas subject 3 has not been able to regulate emotions, this is seen from the characteristics of subject 3 who are rarely present, rarely collect assignments, rely on assignments to friends, therefore subject 3 is not able to control their emotions well. So it can be concluded that subject 1 and 2 generate positive emotions and subject 3 raises negative emotions.